2021
DOI: 10.14295/transportes.v29i4.2456
|View full text |Cite
|
Sign up to set email alerts
|

Structural sensitivity of an asphalt pavement to asphalt binder content and mix design method

Abstract: The goal of this study was to analyze the structural sensitivity of a flexible pavement, whose asphalt layers underwent variations in its mechanical properties due to the asphalt binder content and the mix design method Marshall and Superpave. A variation of ±0.5% within the optimum asphalt binder contents was used (service tolerance) considering possible permissible variations in the asphalt binder content during the asphalt mixture manufacturing process. The values of resilient modulus and indirect tensile s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 7 publications
(10 reference statements)
1
2
0
Order By: Relevance
“…Poor gradation of aggregates resulting in low stability and flow as well as excess voids in the concrete was apparent and capable of inducing pavement failure. This results agreed with the works of similar authors including [3], [6] and [16]. Voids of the order of 6.0 % and flow of 6.3 mm observed along Ado -Ikere road with associated poor stability as low as 320 kg could compromise the integrity of the asphaltic concrete for road construction within the given geological environment.…”
Section: Iv2 Influence Of Gradationsupporting
confidence: 92%
“…Poor gradation of aggregates resulting in low stability and flow as well as excess voids in the concrete was apparent and capable of inducing pavement failure. This results agreed with the works of similar authors including [3], [6] and [16]. Voids of the order of 6.0 % and flow of 6.3 mm observed along Ado -Ikere road with associated poor stability as low as 320 kg could compromise the integrity of the asphaltic concrete for road construction within the given geological environment.…”
Section: Iv2 Influence Of Gradationsupporting
confidence: 92%
“…It was revealed that the permanent deformations of asphalt concrete can influence its mechanical response of materials. Carmo et al, (2021), [6] studied the strength sensitivity of asphalt concrete pavement, which exhibits variations in its mechanical properties due to the changes of asphalt cement binder content. A variation in the binder of ± 0.5% within the optimum asphalt contents was implemented as a service tolerance during the asphalt mixture preparation process.…”
Section: Introductionmentioning
confidence: 99%
“…Carmo et al, (2021) assessed the structural sensitivity of asphalt concrete, which can show variations in the mechanical properties due to the variations of asphalt cement binder content. The indirect tensile strength was implemented as an indicator for the structure analysis.…”
mentioning
confidence: 99%